2017
DOI: 10.1038/s41598-017-06530-3
|View full text |Cite
|
Sign up to set email alerts
|

Trainee Surgeons Affect Operative Time but not Outcome in Minimally Invasive Total Hip Arthroplasty

Abstract: Training of young surgeons in total hip arthroplasty (THA) is crucial, but might affect operative time and outcome especially in minimally invasive (MIS) THA. We asked whether the learning curve of orthopaedic residents trained on MIS THA has an impact on (1) operative time (2) complication rates and (3) early postoperative outcome. In a retrospective analysis of over 1000 MIS THAs from our institutional joint registry, operative time, complication rates, patient reported outcome measures (Western Ontario and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 32 publications
0
22
0
3
Order By: Relevance
“…One study reported outcomes following minimally invasive THA. 15 Dates of publication for included studies ranged from 2004 to 2017. All studies were performed in developed-world settings, with four British, one German, one North American and two Australasian studies.…”
Section: Resultsmentioning
confidence: 99%
“…One study reported outcomes following minimally invasive THA. 15 Dates of publication for included studies ranged from 2004 to 2017. All studies were performed in developed-world settings, with four British, one German, one North American and two Australasian studies.…”
Section: Resultsmentioning
confidence: 99%
“…The difference is due to a higher complication rate of minimal complications, such as a simple urinary tract infection [25] or a slight hypokalemia [26]. A far more important finding is the similar rate of surgical complications, especially considering other studies mostly favor standard approaches [16, 20], regardless of the presence of the learning curve [27]. The lack of differences between the two groups suggests that experienced surgeons have a low fracture rate altogether, regardless of the approach [20, 28, 29].…”
Section: Discussionmentioning
confidence: 99%
“…The demand for minimally invasive hip arthroplasty is continuously increasing [ 15 ]. Literature provides evidence for a decreased intra-operative blood loss, lower postoperative pain levels and a shorter recovery time in case of minimally invasive surgery [ 3 5 ].…”
Section: Discussionmentioning
confidence: 99%